Comparación de la resistencia al deslizamiento en brackets de autoligado y brackets convencionales ligados con ligadura elastomérica convencional y ligaduras de baja fricción - Nieto-Uribe, Mileny; Barrera-Chaparro, Judith Patricia; González-Cáceres, Ernesto José; Parra-Mazo, Ivón Lilian; Rodríguez-Quijada, Aleida Cristina (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: It is important for the orthodontist to be familiar with the sliding resistance (SR) generated by the ligation method used during the space closure phase with sliding mechanics. The objective of this article is to make an in vitro comparison of the SR produced by a self-ligating bracket and a conventional bracket in combination with low-friction and conventional elastomeric ligatures. Methods: SmartClip (3M®) self-ligating brackets and Gemini (3M®) conventional brackets were used, as well as two types of low-friction elastomeric ligature: Slide (Leone®) and Synergy (RMO®), and one type of conventional elastomeric ligature: Sani-Tie (GAC®).The brackets ligation systems were tested with stainless steel wire of 0.019 × 0.025” caliber. Sliding resistance of the bracketwire- ligature combination was measured with an experimental model of three brackets bonded in an acrylic plate mounted on an Instron machine. Each combination was tested nine consecutive times in dry state. Results: The Gemini (3M®) rackets with a conventional Sani-Tie (GAC®) ligature reported mean values of 67.3 g, while the Gemini (3M®) brackets with low-friction Synergy (RMO®) silicone ligature obtained mean values of 84.6 g. The SmartClip (3M®) and Gemini (3M®) brackets with low-friction Slide (Leone®) elastomeric ligature had similar mean values of 5.0 and 5.4 g respectively, with no significant differences (p = 0.999). Conclusions: The Slide (Leone®) low-friction elastomeric ligatures showed sliding resistance forces similar to the SmartClip (3M®) self-ligating brackets.